The influence of leadership traits toward leadership behavior amongst imams in Peninsular Malaysia - Mahazan, Abdul Mutalib @ Taib (2012)
This study aimed to investigate significant traits of leaders that have potential to predict effective leadership behavior of imams in Peninsular Malaysia. Based on some theories and researches concerning leadership traits and behavior, a research theoretical framework to investigate leadership traits and behavior association was designed for this study. The imams’ general cognitive ability, personality, and religiosity were hypothesized as distal leadership traits while leadership experiences, and motivation to lead were hypothesized as mediating leadership traits. In addition, this research also investigated the moderating influence of job autonomy toward the leadership traits and behavior relationship. This study was conducted by using the survey approach. A structured, Malay version-self-administered questionnaire was distributed to 206 randomly selected imams around Peninsular Malaysia. Results of the hierarchical regression analysis revealed that the traits of imams investigated explained 36.1% variance (R²) of the imams’ leadership behavior. Specifically, the analysis demonstrated the imams’ personality and motivation to lead have significant potential to influence the imams’ leadership behavior in positive direction. Past leadership experiences showed potential to influence leadership behavior of imams significantly in negative direction. This research found the imams’ general cognitive ability, religiosity, and job autonomy did not have potential to influence leadership behavior significantly. In addition to the above, this research found motivation to lead partially mediated the influence of personality toward leadership behavior and the variable did not have significant potential to mediate the influence of general cognitive ability and religiosity toward leadership behavior. The same insignificant mediating influence was found for past leadership experiences. Moreover, this research also found high and low job autonomy did not have potential to moderate the influence of leadership traits toward leadership behavior significantly. Overall, results gained in this research could be generalized to the whole population of imams in Peninsular Malaysia and could be useful to assist future selection and training of imams. In addition, this research also provides some information concerning leadership of religious leaders in Peninsular Malaysia. Finally, this research could also provide some information concerning the potential influence of leaders’ religiosity toward leadership behavior as compared to other well-identified leadership traits